The Pragmatics of Emotions in Interlinguistic Healthcare Settings - Farini, Federico (Research in Language, 2013)
Data-based studies on interlinguistic medical interaction show that frequently migrant patients encounter difficulties in expressing their emotions and concerns. Such difficulties are not always overcome through the intervention of an interpreter, as emotional expressions tend to “get missed” in translations which focus on problems and treatments in medical terms. The main question addressed here is: what types of interpreters’ actions cut out, or make relevant, migrant patients’ emotions? Our data is based on a corpus of 300 interlinguistic medical interactions in Arabic, Mandarin Chinese and Italian in two public hospitals in Italy. The conversations involve one Italian healthcare provider, an interpreter and a migrant patient. The corpus is analyzed drawing upon Conversation Analysis, studies on Dialogue Interpreting and Intercultural Pragmatics.